30 days & thirty ways of doing good - Smith, Maurice (Rising River Media, 2018)
"30 days and 30 ways of doing good is your daily guide on a journey through issues affecting our community, with articles written by people who are hands-on involved and making a difference. Take your church, Sunday school class, youth group or service club on a 30 day tour through: hunger, human trafficking, veteran, adoption and foster care, at-risk youth, homelessness and poverty, justice, refugees, seniors, and much more. Discover practical steps to get involved, to make a difference and to engage in kindness and good deeds toward those in need. And be prepared to be personally challenged with a daily spiritual reflection that calls each of us to think higher thoughts about serving those in need."-- back cover